A matter of trust - Warren, Susan May, 1966- (Warren, Susan May, 1966- Montana rescue, 2017)
Champion backcountry snowboarder Gage Watson left the limelight behind and remade his life as a ski patrol in Montana's rugged mountains, as well as serving on the PEAK Rescue team. Senator and former attorney Ella Blair spends much of her time in the limelight. She has a secret-- one that cost Gage his snowboarding career-- and she wants to atone. When Ella's brother goes missing on one of Glacier National Park's most dangerous peaks, Gage isn't sure he wants to help the woman who destroyed his life. As old sparks relight, can they learn to trust each other-- even when disaster happens again?